Perlindungan Hukum bagi Hak Pilih Pemilih Khusus Berdasarkan Peraturan Komisi Pemilihan Umum Nomor 9 Tahun 2019 tentang Pemungutan dan Penghitungan Suara pada Pemilihan Umum di Kabupaten Kampar Tahun 2019 - Azmi, Man; Miswar, Miswar; Sutrisno, Hafiz (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
Legal protection in the sense that in addition to guaranteeing individual rights, must also determine the procedural way to obtain protection of the rights guaranteed to be one of the constitutional rights of citizens who have been recognized as part of human rights. Special Voter List is a list of voters who have a resident identity qualified as voters but have not been registered with the Permanent Voter List. Is the Protection of Special Voter suffrage Law in Kampar Regency in 2019 in accordance with Election Commission Regulation No. 9 of 2019 on Voting and Counting of Votes in General Elections. What are the Constraints of the Kampar District Election Commission in providing Special Voting Rights Legal Protection. What is the Form of Protection of Special Voter suffrage Law based on General Election Commission Regulation No. 9 of 2019. This type of research is the obesity of the field by way of survey. The nature of this researcheris adescriptive method. The ineffectiveness of Special Voters votes an hour before voting ends. If there is intentionalityor negligence that harms the suffrage of Indonesian citizens, Bawaslu conveyed the findings to be followed up by the Election Commission.